Edible Macrofungi in Plant Genetic Conservation Area, Chanthaburi Province: Auricularia cornea strain RSPG5 Fruiting Body Formation and Nutritional Value - Wanich, Uracha; Kunsook, Chutapa; Kanjanavas, Pornpimon; Thanyaponl, Pornpailin; Boonmee, Onanong; Apinansawat, Narumon; Panisan, Thassapol; Surawut, Saowapha (Science & Technology Asia, 2024)
This study aimed to survey the edible macrofungi found in the Plant Genetic Conservation Area of Chanthaburi province, and to study bag cultivation and nutritional value of the Auricularia cornea RSPG5 strain. The molecular identification by internal transcribed spacer ( ITS) region analysis revealed that the strains of RSPG1-11 were identified as Cookeina sulcipes, Cookeina tricoloma, Termitomyces cylindricus, Schizophyllum commune, Auricularia cornea, Amauroderma rugosum, Dacryopinax spathularia, Tremella fuciformis, Pleurotus giganteus, Hohenbuehelia sp., and Phallus lutescens, respectively. Auricularia cornea RSPG5 was selected for the investigation of bag cultivation. The average weight of their mature fruiting body was 69.92±24.79 g/bag, yield data was 87.40 g/kg, and biological efficiency was 8.74. The moisture per 100 g was 87.30 g. The fruiting body contained 0.63 g of protein, 0.04 g of fat, 0.16 g of ash, 11.88 g of carbohydrate, and 11.66 mg of calcium. The total energy was 50.38 kcal /100 g.